The Role of Tim-3 on dNK Cells Dysfunction During Abnormal Pregnancy With Toxoplasma gondii Infection - Li, Teng; Cui, Lijun; Xu, Xiaoyan; Zhang, Haixia; Jiang, Yuzhu; Ren, Liqin; Yang, Chunyan; Liu, Xianbing; Hu, Xuemei (Frontiers in Cellular and Infection Microbiology, 2021)
Vertical transmission of Toxoplasma gondii (T. gondii) infection during gestation can result in severe complications such as abortion, congenital malformation, fetal teratogenesis, etc. Immune inhibitory molecule Tim-3, discovered to be expressed on some decidual immune cells and participates in the maintenance of maternal-fetal tolerance. Dysregulation of Tim-3 expression on decidual NK (dNK) cells was observed in several cases of pregnancy complications, whereas the role of Tim-3 on dNK cells during T. gondii infection remains unclear. In present study, T. gondii infected Tim-3-/- pregnant mice and anti-Tim-3 neutralizing antibody treated and infected human dNK cells were successfully established to explore the role of Tim-3 in dysfunction of dNK cells during abnormal pregnancy. Our results illustrated that Tim-3-/- pregnant mice displayed more worse pregnancy outcomes with T. gondii infection compared to infected WT pregnant mice. Also, it demonstrated that Tim-3 expression on dNK cells was significantly down-regulated following T. gondii infection. Data suggested a remarkable activation of dNK cells in Tim-3-/- mice and anti-Tim-3 neutralizing antibody treated and infected group, with higher ratios of activating receptor NKG2D to inhibitory receptor NKG2A or KIR2DL4, IFN-γ/IL-10, and increased granule production compared with that of infected group. Mechanism analysis proved that T. gondii-induced Tim-3 down-regulation significantly activated the PI3K-AKT and JAK-STAT signaling pathway, by which the GranzymeB, Perforin, IFN-γ and IL-10 production were further up-regulated. Our research demonstrated that the decrease of Tim-3 on dNK cells caused by T. gondii infection further led to dNK cells function disorder, which finally contributed to the development of abnormal pregnancy outcomes.